L’élection présidentielle de février 2019 au Sénégal - Mamadou Bouna Timera; Momar Diongue; Ousmane Thiam (EchoGéo)
The article analyzes the presidential election of February 2019 in Senegal. It describes the pre-election context and focuses on the process and results of the polls with a look back at the implications of the unfolding context. The analysis combines two methodological approaches: an interpretative approach based on context observation and a descriptive approach based on the collection and mapping of statistical data published by the Constitutional Council of Senegal. The results of the study show that the presidential election and its context were marked by a politico-judicial crisis that favored a reconfiguration of the political landscape with the disappearance of the competition of historical parties and the emergence of a new political figure which is the forerunner of the "antisystem". Although the ruling party's candidate was renewed, the results of the vote did not show large geographical disparities between the power and the opposition. Convinced of a territorial balance of power in the vote, the opposition is more by the existence of "conquered territories", which foreshadowed a post-election crisis. In addition, the regional vote or electoral regionalism as well as the partisan position of the media were essential aspects of this election.